2007
DOI: 10.1111/j.1467-789x.2006.00306.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of obesity in 4–18‐year‐old population in the Basque Country, Spain

Abstract: The objective of the study was to estimate the prevalence of overweight and obesity in children and adolescents in the Basque Country, Spain. It consisted of an analysis of baseline data of the Nutrition Survey, a cross-sectional study, carried out in 2004-2005. The study population comprised child and adolescent living in the Basque Country. The analysis was carried out in a representative random sample of 1178 people aged 4-18 years. Anthropometric examinations were undertaken by trained observers using stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 24 publications
(29 reference statements)
3
8
0
4
Order By: Relevance
“…Comparison of our data with reports from other countries has shown that prevalence of overweight and obesity in our region was lower than those reported from European countries, from US and some Asian countries (2, 5, 7, 13, 28). …”
Section: Discussionsupporting
confidence: 46%
“…Comparison of our data with reports from other countries has shown that prevalence of overweight and obesity in our region was lower than those reported from European countries, from US and some Asian countries (2, 5, 7, 13, 28). …”
Section: Discussionsupporting
confidence: 46%
“…Because of the fact that there are many regional disparities both in the obesity prevalence and its temporal changes caused by the complicated interactions of many regional factors, it is not easy to compute reliable national estimates by using the overall criteria [18,48]. Instead, by using the gradient-analyzing method, we first calculated the cases according to the prevalence of overweight and obesity in the sex-age subgroups (Tables 2 and 3), then summarized the total cases for each of the ten regions.…”
Section: Discussionmentioning
confidence: 99%
“…A study of an 11- to 14-year-old population in a city in the Basque Country (northern Spain) classified 7.2% as obese and found a higher prevalence of overweight and obesity among males than females [29]. A study of a younger Spanish population (6–8 years) reported a higher prevalence of overweight (18 vs. 15.7%) and obesity (10.5 vs. 9.4%) among females than males [30].…”
Section: Discussionmentioning
confidence: 99%